Synergistic effects of recombinant expressed Fowlicidin and Thymosin α1 hybrid peptides in modulating inflammation and infection in avian macrophages - Baseer Ahmad; Baseer Ahmad; Zaheer Abbas; Wei Xubiao; Kashif Hussain; Atif Rehman; Si Dayong; Asghar Abbas; Christina Hölzel; Zhang Rijun (Frontiers in Microbiology)
The hybrid FowlTα1 peptide represents a promising biomolecule synthesized from two naturally occurring peptides, namely Fowlicidins (Fowl) and Thymosin α1 (Tα1). This particular peptide exhibits remarkable anti-inflammatory and antimicrobial properties and demonstrates the capacity to effectively interact with lipopolysaccharide (LPS), while simultaneously inducing minimal cytotoxicity and hemolytic repercussions. Despite its potential, the high cost of this peptide has limited its use. To overcome this limitation, the present study developed a cost-effective and biocompatible method for expressing the FowlTα1 peptide in Pichia pastoris (P. pastoris). We obtained a transgenic strain of the hybrid FowlTα1 peptide with a predicted molecular weight of 3.1 kDa. The FowlTα1 peptide was purified followed by reverse-phase high-performance liquid chromatography (RP-HPLC), yielding 7.2 mg with a purity of 98.2%. Furthermore, physiochemical and structural analysis revealed an amphipathic helical configuration that enhances bioactivity. Moreover, in LPS-stimulated HD11 macrophages, the hybrid FowlTα1 peptide significantly reduced the release of nitric oxide (NO), TNF-α, IL-6, and IL-1β in a dose-dependent manner (p < 0.05) and displayed robust antimicrobial activity against Escherichia coli (E. coli) compared to conventional antibiotic. Overall, the results of this study highlighted the production method and potential of the FowlTα1 peptide as a novel therapeutic agent for antimicrobial, anti-inflammatory, and anti-endotoxin applications.